Метаболічні процеси в печінці щурів за експериментального діабету та впливу цитрату хрому - Іскра, Руслана; Слівінська, Оксана; Шатинська, Олена; Сварчевська, Оксана; Сеньків, Оксана; Пилипець, Андрій; Iskra, Ryslana; Slivinska, Oksana; Shatynska, Olena; Svarchevska, Oksana; Senkiv, Oksana; Pulipez, Andriy (Східноєвропейський національний університет імені Лесі Українки, 2015)
Установлено, що за умов додавання до раціону щурів зі стрептозотоцин-індукованим діабетом цитрату хрому в кількостях 10 і 25 мкг Cr/кг маси тіла зростає активність лактатдегідрогенази, глюкозо-6-фосфатде- гідрогенази, каталази, глутатіонпероксидази, уміст відновленого глутатіону та знижується вміст продуктів пероксидного окиснення ліпідів у печінці. Under the condition of diabetes mellitus an energetic exhaustion of organism is observed, which leads to the deficiency of energetic substrates and it affects the effectiveness of antioxidant system functioning in direct proportion. Under the condition of experimental diabetes credible increase of MDA content, decrease of catalase, glutathione peroxidase, lactate dehydrogenase activities and the content of reduced glutathione were established in liver tissue of rats. After the addition of chromium citrate in a quantity of 10 and 25 mcg Сr3 + /kg body weight to the diet of rats those researched indexes reach to their levels in the control group, while activities of lactate dehydrogenase, glucose-6-phosphate dehydrogenase, catalase, glutathione peroxidase and the content of the reduced glutathione increase compared to rats with experimental diabetes, although the content of lipid peroxidation products decrease.
Metabolic Processes in rats’ Liver Under the Condition of Experimental Diabetes and Chromium Citrate Influence.
Keywords: щурі; цитрат хрому; експериментальний діабет; печінка; rats; chromium citrate; experimental diabetes; liver